The effect of aging and gender on plantar pressure distribution during the gait in elderly - Gimunová, Marta; Zvonař, Martin; Mikeska, Ondřej (Acta of bioengineering and biomechanics, 2018)
PURPOSE: The effect of age on structural foot characteristics as well as on the plantar pressure distribution has been shown previously. However, the number of studies focused also on gender gait differences of elderly is lacking. The purpose of this study was to compare dynamic gait characteristic in younger and older elderly and to investigate the gender differences as the life-long load and footwear choice differ in males and females. METHODS: 61 healthy elderly participants were divided by age and gender into four groups: males 60-69, males 70-79, females 60-69 and females 70-79 years old. Plantar pressures were recorded during barefoot walking at naturally chosen speed using Emed-at (Novel GmbH, Germany). Three steps of the left foot of each participant were used for further analysis, furthermore, hallux angle, foot progression angle, and arch index were calculated by the Emed software from obtained foot- prints. To compare the differences between the analyzed groups, effect size obtained by Cohen's d was used. RESULTS: Comparing the two age male groups, higher mean pressure was found in the 70-79 age group in region MH4, MH5 and mid-foot, suggesting a greater lateral load and decreased longitudinal arch of the foot. Comparing female groups, the higher mean pressure was found in the older age group in region MH1. In all other regions, the mean pressures were reduced in the older groups. CONCLUSIONS: The results suggest that the effect of aging on plantar pressure distribution during the gait is affected by gender and should be considered when evaluating the gait of elderly.
Keywords: Sex Factors; Humans; lidé středního věku; Confidence Intervals; Female; interval spolehlivosti; Aged; Pressure; chůze (způsob); věkové faktory; tlak; senioři; lidé; noha (od hlezna dolů); Gait; sexuální faktory; ženské pohlaví; Male; Middle Aged; Foot; Age Factors; mužské pohlaví